2018
DOI: 10.5324/njsts.v6i1.2520
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Adequate Competencies for the Future

Abstract: Digital skills are a prerequisite today for working, studying, civic participation, and maintaining social relationships in our digitalised technical world. These skills are also important both as a general goal and an instrument for learning. This study briefly presents the aims that are related to digital skills of the Finnish curricula, and explores, using a large sample (N = 3,206) of Finnish upper secondary school students, these young people’s digital skills and their distribution. The study provides new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For example, Dijk and van Deursen (2014) have criticised the apparent overestimation of young people's digital competences. Kaarakainen et al (2018) found in their study that the average performance level for Finnish upper secondary school students in the ICT skills test was relatively low, as on average these students had mastered only one-third of the skills being tested. It is interesting to see how new national descriptions of ICT competence, media literacy and programming skills in primary schools (National Audiovisual Institute and Finnish National Agency for Education, 2021) will affect the development of ICT skills and also ICT skills selfassessment for younger age groups.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Dijk and van Deursen (2014) have criticised the apparent overestimation of young people's digital competences. Kaarakainen et al (2018) found in their study that the average performance level for Finnish upper secondary school students in the ICT skills test was relatively low, as on average these students had mastered only one-third of the skills being tested. It is interesting to see how new national descriptions of ICT competence, media literacy and programming skills in primary schools (National Audiovisual Institute and Finnish National Agency for Education, 2021) will affect the development of ICT skills and also ICT skills selfassessment for younger age groups.…”
Section: Discussionmentioning
confidence: 95%
“…It is important to recognize that in the field of Health and Welfare the majority of students (in our study 79.9%) are typically female. Earlier research has concluded that, although there is no actual difference between the genders in terms of upper secondary school students' ICT skills (Kaarakainen et al, 2018), there are undoubtedly gender differences in the rating of personal computer and internet skills (Hakkarainen et al, 2000;Hargittai & Shafer, 2006). In addition to the fact that ICT skills play an important role in the field of Information and Communication Technologies, it is also worth noting that this is an area where the majority of respondents (90.6%) in this survey were male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these circumstances, the research's primary goal is to explore the digital divide's influence on accounting students' digital competence. Digital competence is the ability to adeptly employ information and communication technology applications within an academic context (Falloon, 2020;Kaarakainen et al, 2018). Previous studies have brought to light the presence of digital access disparities among Indonesian accounting students (Lythreatis et al, 2019;Qi et al, 2023;Rahardjo et al, 2016;Winardi & Anggraeni, 2017).…”
Section: Introductionmentioning
confidence: 99%